Метапоэтика экфрастических импульсов и жестов в прозе самого «неэкфрастичного» писателя: А.П. Чехов и его «не-экфрасисы» - АВТУХОВИЧ, ТАТЬЯНА ЕВГЕНЬЕВНА (SlavVaria, 2021)
Metapoetics of ekphrastic impulses and gestures in the prose of the most “non-ekphrastic” writer. The article analyzes ekphrases as well as ekphrastic impulses and gestures in Chekhov's short stories. It is shown that ekphrases perform an important function in the works of the writer, being a significant part of the artistic whole. It is concluded that the analysis of ekphrastic inclu-sions in the aspect of the author's metapoetics indicates a constant change in the artistic language, which is associated with a change in the type of ekphrasis (from mimetic to non-mimetic) and its function in the literary work: from the plot-forming function to the situation modeling function, and then to the invisi-ble hint function, suggesting active interaction between the author and the reader.